ANALISIS MASALAH PENILAIAN HASIL BELAJAR DENGAN PENDEKATAN TEORI KOGNITIF DAN KONSTRUKTIF - Sabrina Jihan Salsabilla; M. Mamduh Winangun (JURNAL ILMIAH NUSANTARA, 2026)
This study investigates the difficulties in assessing educational learning outcomes through cognitive and constructivist theoretical frameworks. It uses a qualitative case study method and looks at secondary data from academic journals, education reports, statistics, and news sources. The main findings show that traditional assessment systems, which focus on final products, don't do a good job of measuring students' advanced thinking skills and deep understanding of concepts. According to learning theory, behaviorism encourages score-driven motivation through reinforcement, cognitivism emphasizes process-oriented cognitive evaluation, and constructivism requires tools to evaluate learners' independent knowledge construction. So, solutions include using real-world methods like projects, portfolios, and Higher Order Thinking Skills (HOTS) tests, along with teaching that focuses on the student. So, assessments of learning outcomes should lead to deeper, more meaningful learning and raise the overall level of education.